Study on enhancing electrochemical properties of Li in layered compound Na0.7Li0.3Mn0.75O2. (10th February 2018) - Yu, Han; Liu, Guoqiang; Li, Guocheng; Zhang, Jingyi; Chen, Gang; Wen, Lei
Abstract: The enhancing sodium ion insertion and deinsertion characteristics of Li in layered structure compound were studied. Layered structure materials Na2/3 Ni1/3 Mn2/3 O2 and Na0.7 Li0.3 Mn0.75 O2 were synthesized. They can be used as cathode materials for sodium ion batteries. Although they displayed same crystal structures, the Na0.7 Li0.3 Mn0.75 O2 exhibited better electrochemical properties than Na2/3 Ni1/3 Mn2/3 O2 . For Na0.7 Li0.3 Mn0.75 O2, when cycled between 2.0 and 4.4 V at a current rate of 17 mA g −1, its charge capacity of reached 175 mAh g −1, and its discharge capacity was 149 mAh g −1 . In the first several charge-discharge cycles, the capacity decreased with cycles performing. Then capacity tended to be stable and began to increase. After 40 cycles, its discharge capacity was 143 mAh g −1 . It discharge capacity could reach 121 mAh g −1 at current rates of 0.34 mA g −1 -charge/0.85 mA g −1 -discharge. Li element enhanced the electrochemical properties such as cycle performance and rate capability.